PENGARUH ADIKSI JUDI ONLINE TERHADAP PENURUNAN INTERAKSI SOSIAL DAN PERILAKU AGRESIF REMAJA DI DESA ADIREJO - Febri Mustofa, Ahmad; Sari, Meita; Sugiarto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of online gambling addiction on the decline in social interaction and aggressive behavior of adolescents in one of the villages in Lampung Province. The study used a quantitative approach with an associative method and an ex post facto correlational design, with a sample of 246 respondents obtained through a purposive sampling technique. Data were collected using the Gambling Urge Scale (GUS) for online gambling addiction and the Social Skills Inventory (SSI) for social interaction and the Buss–Perry Aggression Questionnaire (BPAQ) for aggressive behavior, which have been tested for validity and reliability. Data analysis used simple linear regression with the help of SPSS version 21. The results showed that online gambling addiction significantly influenced social interaction and aggressive behavior with a significance value <0.05. The coefficient of determination showed that online gambling addiction contributed 27.9% to social interaction and 33.3% to aggressive behavior. Thus, it can be concluded that online gambling has a negative impact on the social and emotional conditions of adolescents.